EVALUASI PEMBELAJARAN BAHASA ARAB DI PERGURUAN TINGGI PARIWISATA - Euis Ernawati (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
Top of FormThis study aims to describe the evaluation of Arabic teaching-learning at STIE Pariwisata YAPARI. The research uses descriptive method with a qualitative approach. The subject of this research are the lecturer of Arabic language and the students on their fourth semester. The data are collected by interview and document analysis as triangulation. In general it can be said that the evaluation is well. All components are synergistic. The purpose of evaluation and competence to be achieved is appropriate. The evaluation reports are processed and published by BAAK directly. Between evaluation and learning objectives are also appropriate.